New tablet formulation of tacrolimus with smaller interindividual variability may become a better treatment option than the conventional capsule formulation in organ transplant patients - Kim YK; Kim A; Park SJ; Lee H (Drug Design, Development and Therapy, 2017)
Yu Kyong Kim,1 Anhye Kim,1,2 Shin Jung Park,3 Howard Lee1,4 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, 2Clinical Trial Center, Ajou University Medical Center, Suwon, 3Research Institute, Chong Kun Dang Pharmaceutical Corp, Yongin, 4Department of Transdisciplinary Studies, Graduate School of Convergence Science and Technology, Seoul National University, Suwon, Republic of Korea Abstract: To evaluate the pharmacokinetic (PK) and tolerability profiles of a new tablet formulation of tacrolimus and its interindividual variability (IIV) in the systemic exposure, and to compare them with those of the conventional capsule formulation, a randomized, open-label, two-treatment, two-period, two-sequence, crossover study was performed in 47 healthy males. The capsule or tablet formulation of tacrolimus was orally administered, and serial blood samples were collected up to 96 hours after dosing. Whole-blood tacrolimus concentration was determined using liquid chromatography–tandem mass spectrometry. The maximum whole-blood tacrolimus concentration (Cmax) and the area under the whole-blood tacrolimus concentration–time curve from 0 hour to the last quantifiable concentration (AUClast) were compared between the two formulations. The similarity factor (f2) of the in vitro dissolution profiles was calculated. The geometric mean ratio (90% confidence interval) of tablet to capsule was 0.9680 (0.8873–1.0560) and 1.0322 (0.9359–1.1385) for Cmax and AUClast, respectively. The IIV of Cmax and AUClast of the tablet was smaller than the capsule. The f2 values were >50 in all media. Both formulations were well tolerated. Thus, the tablet formulation of tacrolimus has smaller IIV in the systemic exposure than capsule, while having comparable PK and tolerability profiles, which may render it as a better treatment option for organ transplant patients. Keywords: new formulation, incrementally modified drug, comparative pharmacokinetics, healthy volunteers, immunosuppressant